Perceptual and Interoceptive Strength Norms for 270 French Words - Miceli, Aurélie; Wauthia, Erika; Lefebvre, Laurent; Ris, Laurence; Simoes Loureiro, Isabelle (Frontiers in Psychology, 2021)
Perceptual experience through the five modalities (i.e. vision, hearing, touch, taste and smell) has demonstrated its key role in semantics. Researchers also highlighted the role of interoceptive information in the grounded representation of concepts. However, to this day, there is no available data across these modalities in the French language. Therefore, the aim of this study was to circumvent this caveat. Participants aged between 18 and 50 completed an online survey in which we recorded scores of perceptual strength (PS), interoceptive information, imageability, concreteness, conceptual familiarity and age of acquisition of 270 words of the French language. We also analyzed the relationships between perceptual modalities and psycholinguistic variables. Results showed that vast majority of concepts were visually-dominant. Correlation analyses revealed that the five PS and the psycholinguistic variables were strongly correlated and highlight that PS variables index one aspect of the semantic representations of a word. On the other hand, high interoceptive scores were highlighted only for the less imageable and less concrete words, emphasizing their importance for the grounding of abstract concepts. Future research could use these norms in the investigation of the role of perceptual experience in the representation of concepts and their impact on word processing.